Diagnostic accuracy of haematological indices in the diagnosis of neonatal sepsis in a resource poor setting: a cross-sectional study - Nnamani, Kenechi O.; Nnamani, Chioma P.; Ezeudu, Chijioke E.; Edokwe, Emeka S.; Elo-Ilo, Jacinta C.; Iloh, Kenechukwu K.; Anyanwu, Onyinye U.; Ekwebene, Onyeka C.; Chigbo, Chisom G.; Ugochukwu, Ebelechukwu F.; Ezechukwu, Clement C. (International Journal of Research in Medical Sciences, 2024)
Background: Where the newer methods for the diagnosis of neonatal sepsis are not available, reliability of simple and inexpensive haematological indices as predictors of neonatal infection becomes useful. This study aimed to determine the sensitivity and specificity of total white blood cell count (TWBC), immature-to-total neutrophil ratio (I/T ratio) and micro-erythrocyte sedimentation rate (micro-ESR) in the diagnosis of neonatal sepsis. Methods: A hospital-based cross-sectional study of 120 neonates hospitalized at the Special Care Baby Unit (SCBU) of a tertiary institution whose parents/caregivers wrote informed consent were recruited while neonates with gross congenital abnormalities (obvious neural tube defects, gastroschisis) and those whose caregivers refused to give consent were not recruited. A proforma was used to document neonatal and laboratory information. Data were analysed, appropriate proportions were used to obtain the sensitivity and specificity of TWBC, I/T ratio and m-ESR. Test of association for categorical variables were done using Chi-square test and T-test for comparison of mean between babies with and without sepsis. P value was set at <0.05. Results: Associations between TWBC, I/T ratio and neonatal sepsis were statistically significant (p=0.015, 0.020 respectively). There was a statistical difference between the mean I/T ratio in babies with and without sepsis. (p=0.032). The sensitivities of I/T ratio, m-ESR and TWBC were 83.2%, 53.3% and 46.7% respectively while their specificities were 40.0%, 61.1% and 76.7% respectively. Conclusions: Hospitals in resource poor-settings, where blood culture cannot be obtained readily, I/T ratio can be used to detect neonatal sepsis.